2009
DOI: 10.1186/1746-6148-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm forming abilities of Salmonellaare correlated with persistence in fish meal- and feed factories

Abstract: Background: Feed contaminated with Salmonella spp. constitutes a risk of Salmonella infections in animals, and subsequently in the consumers of animal products. Salmonella are occasionally isolated from the feed factory environment and some clones of Salmonella persist in the factory environment for several years. One hypothesis is that biofilm formation facilitates persistence by protecting bacteria against environmental stress, e.g. disinfection. The aim of this study was to investigate the biofilm forming p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
184
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(212 citation statements)
references
References 28 publications
12
184
4
1
Order By: Relevance
“…These biofilms allow the persistence of Salmonella spp. in feed and food factory environments for months, and even years (Vestby et al, 2009;Schonewille et al, 2012;Prunić et al, 2016).…”
Section: B I O F I L M F O R M I N G C a Pa C I T Y O F Salmonella Spmentioning
confidence: 99%
“…These biofilms allow the persistence of Salmonella spp. in feed and food factory environments for months, and even years (Vestby et al, 2009;Schonewille et al, 2012;Prunić et al, 2016).…”
Section: B I O F I L M F O R M I N G C a Pa C I T Y O F Salmonella Spmentioning
confidence: 99%
“…This enables the growth of anaerobic and microaerophilic bacteria in biofilm and thus provides advantageous conditions for the development of biofilms. It was determined that the occurrence of rigid pellicle structure requires a regulation of the functionality of the genes that are effective on the biofilm formation (Stepanović et al, 2004;Latasa et al, 2005;Vestby et al, 2009). In the trials investigating the effect of created mutations on the pellicle structure, no change in the properties of the pellicle structure was determined in rmbA, fidL, misL, yliH, fliC, yliH, and cheM gene mutants when compared to the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation assay was performed in 96-well polystyrene microtiter plates according to the method described by Woodward et al (2000), with some slight modifications as suggested by Stepanović et al (2000) and Vestby et al (2009). Briefly, overnight cultures were diluted in LB without NaCl (LB wo /NaCl) to OD 595 = 0.2, and 30 µL of this suspension was transferred to each well of the polystyrene plates containing 100 µL of LB wo /NaCl (3 parallels of each strain).…”
Section: Microtiter Plate Assaymentioning
confidence: 99%
“…however, this serovar was frequently detected in animal feed, which is a gate for microbial entrance into the food chain. Non-typhi serotypes of Salmonella enterica from feeds induce colonization or infection in foodproducing animals, hence posing an indirect risk for human health (CrumP et al, 2002;ALVAREZ et al, 2003;PAPADoPouLou et al, 2009;VESTBy et al, 2009). apparently, serovars present in animal feed differ from those commonly identified in humans, which is most probably because different strains survive in different environments (ALVAREZ et al, 2003).…”
Section: Congo Red Agar Test All S Tennessee Isolates (mentioning
confidence: 99%
“…The biofilm organization pattern of salmonellas is most likely responsible for their increased resistance to a range of stress factors, such as long-term desiccation, low nutrients, and disinfectants from feed and the food factory environment AVILES et al, 2013). Such multicellular behavior (biofilm) enables salmonellas to persist in the feed factory environment for months, even years (NeSSe et al, 2003;VESTBy et al, 2009;møretrø et al, 2009). Salmonella biofilms from equipment and food contact surfaces are a well-established source of long-lasting contamination of final products, which has been repeatedly confirmed by molecular methods (NeSSe et al, 2003;PAPADoPouLou et al, 2009). In Great Britain, S. Tennessee is one of the top five most isolated serovars from feed for cattle, pigs and poultry (PAPADoPouLou et al, 2009).…”
mentioning
confidence: 99%